Возвращение Бешеного: [роман] / Виктор Доценко - Доценко Виктор Николаевич (Вагриус, 1996)
Экземпляры: ф.1 (2012) / Инвентарный номер: 54960 / Цена: 196.57 / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Д 71 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44